1988
DOI: 10.1159/000215838
|View full text |Cite
|
Sign up to set email alerts
|

Reference Values and Variability of Plasminogen in Healthy Blood Donors and Its Relation to Parameters of the Fibrinolytic System

Abstract: During a survey of four month’s duration the following parameters were determined in 43 healthy blood donors (22 males, 21 females; mean age 29 years /20 – 49/): plasminogen activity, plasminogen concentration, α2-antiplasmin (α2-AP) activity, α2-AP concentration, tissue type plasminogen activator (t-PA) activity, t-PA concentration, plasminogen activator inhibitor – I (PAI-I) activity, AT III activity, AT III concentration and heparin cofactor II (HC II) activity. Normal value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 8 publications
1
9
0
Order By: Relevance
“…This range of calibration allows the determination of normal range of hPIg concentrations in 130 adult plasma (mean = 101 mg/L, k 2 SD range = 54-1 48 m a ) , and covers published values for healthy adults (means between 100 and 120 mg/L), new boms (about 50% lower), and pathological increased or decreased levels associated with hereditary disorders, inflammation, and hepatitis (29)(30)(31)(32)(33). Moreover, the risk of analyte underevaluation in Table 1.…”
Section: Discussionmentioning
confidence: 67%
“…This range of calibration allows the determination of normal range of hPIg concentrations in 130 adult plasma (mean = 101 mg/L, k 2 SD range = 54-1 48 m a ) , and covers published values for healthy adults (means between 100 and 120 mg/L), new boms (about 50% lower), and pathological increased or decreased levels associated with hereditary disorders, inflammation, and hepatitis (29)(30)(31)(32)(33). Moreover, the risk of analyte underevaluation in Table 1.…”
Section: Discussionmentioning
confidence: 67%
“…Flow cytometric analyses have shown that all three receptors are present at the meningococcal surface, but at low levels. However, it is well known from other bacterial pathogens that plasminogen receptors can be present at the cell surface at very low levels, as plasminogen is highly abundant in many body fluids (serum concentrations, ϳ1.6 to 2 mol/liter, roughly corresponding to 100 to 200 mg/liter) (2,12,35,39). The presence of pneumococcal enolase, which has been shown to act as the major plasminogen receptor of S. pneumoniae, at the surfaces of these bacteria has been studied in detail (29).…”
Section: Discussionmentioning
confidence: 99%
“…5 In the extravascular space, PLG has many other functions, including roles in angiogenesis, inflammation, and tissue remodeling. 6,7 PLG levels vary approximately 2-fold among healthy individuals, 8 and this variation is influenced by inherited factors. A genome-wide linkage study of PLG levels in 629 individuals in 26 Mexican American families estimated the heritability of PLG to be 43% 9 and identified a region on chromosome 12 (Chr12) with suggestive linkage (LOD 5 2.73).…”
Section: Introductionmentioning
confidence: 99%